2013
DOI: 10.3126/ajms.v3i3.5240
|View full text |Cite
|
Sign up to set email alerts
|

Mucinous carcinoma of breast: FNAC as effective diagnostic modality

Abstract: Mucinous carcinoma of the breast in pure form comprises only 2% of all breast cancers. Pure mucinous carcinoma of the breast have better prognosis. They are usually having higher incidence in peri-menopausal and post-menopausal age group. We report a 32-year-old female, clinically suspected to have benign breast disease, diagnosed as mucinous carcinoma of the breast on FNAC. In such cases, there is always a high probability of missing the diagnosis at imaging because of the absence of established radiological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…SRC, mucinophages, and MVF were rarely observed. [5][6][7] Review of the literature revealed majority of the published literature pertaining to the cytological diagnosis MC are single case reports with only few series available. [6][7][8][9][10] Adhikari et al 7 studied eight cases of MC (5 PMC + 3 MMC) and observed presence of ECM along with single and cluster of tumor cells floating in them and thin walled capillaries as prominent features in five cases of PMC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SRC, mucinophages, and MVF were rarely observed. [5][6][7] Review of the literature revealed majority of the published literature pertaining to the cytological diagnosis MC are single case reports with only few series available. [6][7][8][9][10] Adhikari et al 7 studied eight cases of MC (5 PMC + 3 MMC) and observed presence of ECM along with single and cluster of tumor cells floating in them and thin walled capillaries as prominent features in five cases of PMC.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the distinct clinicopathological parameters their exists prognostic difference between PMC and MMC. [1][2][3][4] Even though fine needle aspiration cytology (FNAC) is well accepted as initial diagnostic modality for breast cancer, 5 the cytological features of PMC are less defined. Cytological diagnosis of PMC is challenging as the features overlap with many benign and malignant lesions.…”
Section: Introductionmentioning
confidence: 99%
“…MC has better prognosis (90% survival at 10 years) and higher incidence in perimenopausal and postmenopausal age groups. The incidence of MC in women under 35 years of age is only 1% [1,6-8]. MC is a slow-growing tumor, with an estimated growth rate of one third of that of IDC.…”
Section: Discussionmentioning
confidence: 99%